Students' Critical Thinking Ability in Solving Story Problems of Three-Variable Linear Equation System - Nurqodri, Zahrani; Setyaningsih, Rini (Journal of Medives : Journal of Mathematics Education IKIP Veteran Semarang, 2024)
This study aims to describe how the critical thinking process of students in solving math problems in the form of story problems of the Three-Variable Linear Equation System (SPLTV). This type of research is descriptive and uses qualitative methods. The subjects in this study were 6 students of class X 5 SMA Batik 1 Surakarta with high, medium, and low categories. Data collection techniques used tests and interviews, which have been declared valid by validators. Indicators of students' critical thinking abilities in research include clarification, assessment, strategy and inference. The results of this study are high category students can fulfill all indicators of critical thinking aspects, namely clarification, assessment, strategies, and inference. Medium category students are only able to fulfill three indicators, namely clarification, assessment, and strategies or only two indicators, namely clarification, and assessment. Low category students are only able to fulfill one critical thinking indicator, namely clarification, while other subjects cannot fulfill any critical thinking indicators. Keywords : critical thinking, math story problems, SPLTV.